Analyzing Young Generation English Learning and Community Empowerment through Zoom-Based Service Program at Alam Daur Community - Irawan, Lalu Ari; Aprillah , Ahmad; Ariawan, Soni; Abidin, M. Zaenal; Habibullah, Bukran; Nazira, Arni; Sukmojati, Edi; Hurniati, Hurniati; Kamarudin, Samsul; Maknun, Joharatil; Lumbantobing, Panca; Payung, Naftalia Fany; Pratiwi, Ika Aditya; Nafiah, Silvia Umrotun; Riza, Yunisa; Septiyani, Winda (Universitas Mataram, 2024)
English language skills are currently considered important as one of the fundamental requirements for continuing an educational career or work. This community service research aims to improve English skills for the younger generation through the Alam Daur Community, a community engaged in literacy in the Central Lombok area. The English Intensive program is implemented online using the Zoom application. The method used was the cooperative learning method, participants were involved in webinar sessions, discussions, conversation simulations, and exercises that were relevant to daily activities and the needs of students. The results of the study showed that the intensive English program carried out for one full month through the zoom platform effectively stimulated children's skills. This could be seen from the post-test results which showed an increase in scores. In addition, other results proved that there was a strong relationship between tutors and participants and a fast exchange of information. Student involvement and motivation as well as increasing teacher capacity were also discussed. In line with Rena Pasick, Wilma Brakefield-Caldwell of Detroit, Michigan, and Edith Parker, this study recommends strong and ongoing collaboration, so that existing changes can be evaluated and treatments can be continuously developed for the institutions and communities involved.